Pharmacokinetic Study of Cefazolin in Short Daily Hemodialysis. Issue 4 (April 2019) - Palmer, Katie; Walker, Scott; Richardson, Robert; Jassal, Sarbjit V.; Battistella, Marisa
Background: A number of centers across the world offer short daily hemodialysis (SDHD) treatments. To date, cefazolin pharmacokinetics have not been described in patients undergoing SDHD.Objective: The purpose of this study was to investigate the effect of SDHD on the pharmacokinetics of cefazolin.Methods: This was a prospective, open-label, pharmacokinetic study of cefazolin during SDHD in 10 noninfected patients. Participants received a 1-g intravenous (IV) infusion of cefazolin after SDHD on study day 1 and a second dose after SDHD on study day 2. To determine the concentration of cefazolin, 6 blood samples were drawn at 0, 1, 2, 2.3, 4, and 24 hours after initiation of dialysis on day 2, and 2 dialysate samples were drawn at 1 and 2 hours after initiation of dialysis on day 2. Samples were analyzed using high-performance liquid chromatography, and pharmacokinetic parameters were determined.Results: Median interdialysis clearance was 0.16 L/h (interquartile range [IQR]: 0.11-0.21 L/h), and median intradialysis clearance was 1.95 L/h (IQR: 1.66-2.45 L/h). Median interdialysis half-life was 28.2 hours (IQR: 23.5-59.3 hours) as compared with a median intradialysis half-life of 2.3 hours (IQR: 1.7-2.7 hours). The median percentage removal of cefazolin during dialysis was 41% (IQR: 35%-53%).Conclusion and Relevance: Estimated cefazolin dialysis clearance is similar to previous estimates with conventional thrice-weekly regimens. Current dosing recommendations of 1 g IV post-SDHD achieve total serum drug concentrations greater than 40 mg/L in all patients, which is the total drug concentration required for bactericidal activity against Staphylococcus species.